A research study into the interactions between the monoherbal formulations of arjuna and Aloe vera in a rat model of isoproterenol-induced cardiotoxicity - Ashish Kushwaha (International Journal of Toxins and Toxics, 2025)
Aloe vera is a herbal dietary supplement, and arjuna is used for its cardioprotective properties. Rats were given isoproterenol hydrochloride subcutaneously to cause myocardial infarction. The purpose of the study was to identify any potential pharmacodynamic interactions between the commercially available formulations of Aloe vera and arjuna. Materials and Procedures: The electrocardiogram (heart rate, ST segment elevation time, QRS complex amplitude), serum cardiac markers (creatine kinase, isoform of creatine kinase, lactate dehydrogenase), blood electrolyte levels, antioxidant enzyme activity (superoxide dismutase, catalase, glutathione), and histopathological findings all confirmed the different tissue damage caused by isoproterenol in different groups. Results: In comparison to the Arjuna group, the interaction group displayed elevated cardiac markers, decreased antioxidant enzyme activity, elevated heart rate, increased ST segment elevation time, and decreased QRS complex. The findings showed statistical significance (p<0.05). Conclusion: When Arjuna and Aloe vera were taken together, the cardioprotective effect of Arjuna was diminished due to the detrimental effect between the two herbal formulations.
Keywords: Aloe vera; Arjuna; Cardiotoxicity; Isoproterenol; Myocardial infarction